Cultivation of Chlorella vulgaris in anaerobically digested gelatin industry wastewater - G. C. Blanco; M. J. Stablein; G. Tommaso (Water Supply, 2021)
This work aimed to study the effect of using anaerobically digested gelatin industry wastewater as a culture medium for the cultivation of Chlorella vulgaris microalgae in bubble column photobioreactors (PBRs). Batch experiments were carried out to determine the growth kinetics by inoculating microalgae in wastewater prepared with different dilutions and supplemented with Bold's Basal Medium (BBM). From the values of the saturation constants (KS = 50.25 mgN-NH4+·L−1) and substrate inhibition (KI = 28.12 mgN-NH4+·L−1) obtained in the adjustment to the Andrews kinetic model (R2 = 0.817), the PBRs achieved specific maximum growth rates (μmax) of 0.343 d−1, biomass productivity of 0.141 g·L−1·d−1, lipid content of 12.45%, lipid productivity of 17.63 mg·L−1·d−1 and instantaneous ammoniacal nitrogen consumption rates of 20.06 and 14.22 mg·L−1·d−1. The addition of wastewater to the culture medium provided an increase in biomass productivity of 57.45% in relation to the negative control. The results obtained demonstrate the high efficiency of C. vulgaris in the removal of nitrogenous compounds and the potential of using anaerobically digested gelatin industry wastewater in the production of microalgae biomass. HIGHLIGHTS The use of wastewater in bubble column photobioreactors (PBRs) provided a 57.45% increase in biomass productivity (PB).; Andrews model successfully predicted the growth kinetics of C. vulgaris in wastewater (R2 = 0.817).; Ammoniacal nitrogen (N-NHx) was preferred compared with nitrate (N-NO3) during the operation of photobioreactors.; The first-order decay model with residual successfully predicted the kinetics of nitrate (N-NO3) consumption.; Two first-order decay models with residuals in series better represented the ammoniacal nitrogen (N-NHx) depletion.;